HUBUNGAN DUKUNGAN KELUARGA DENGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA ANGGOTA KELUARGA DI WILAYAH KERJA PUSKESMAS LEMBANG PADA MASA PANDEMI COVID-19 - Erviana Miswarman; Yunel Maylianti; Muhammad Taufik Page (AKPER Pemkab Purworejo, 2022)
ABSTRACT The ever-increasing number of confirmed cases of COVID-19 has made people aware to take precautions. Public awareness will make the transmission of this disease will decrease. Prevention of COVID-19 can be done by implementing clean and healthy living behavior at home that can be done by every family member. The role of family support is very important for every family member in practicing clean and healthy living behavior so that the family avoids various diseases including COVID-19. The purpose of this study was to determine the relationship between family support and clean and healthy living behavior for family members in the working area of ​​the Lembang Public Health Center during the COVID-19 pandemic. The research method is an analytic survey with a cross sectional approach. The population is 4344 families in the working area of ​​the Lembang Health Center. The number of samples is 98 families. The sampling technique used is probability sampling with a simple random sampling approach. The results of the Chi square statistical test obtained p value = 0.000 (p <0.05), this means that the hypothesis is accepted, namely there is a relationship between family support and clean and healthy living behavior in family members in the Lembang Health Center working area during the COVID pandemic. -19.